2017
DOI: 10.1371/journal.pone.0178034
|View full text |Cite
|
Sign up to set email alerts
|

Intercenter validation of a knowledge based model for automated planning of volumetric modulated arc therapy for prostate cancer. The experience of the German RapidPlan Consortium

Abstract: PurposeTo evaluate the performance of a model-based optimisation process for volumetric modulated arc therapy applied to prostate cancer in a multicentric cooperative group. The RapidPlan (RP) knowledge-based engine was tested for the planning of Volumetric modulated arc therapy with RapidArc on prostate cancer patients. The study was conducted in the frame of the German RapidPlan Consortium (GRC).Methods and materials43 patients from one institute of the GRC were used to build and train a RP model. This was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 24 publications
(13 reference statements)
1
78
0
Order By: Relevance
“…Knowledge‐based radiotherapy treatment planning is deemed to reduce the inter‐planner varieties of plan quality1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 and expedite the planning process 14, 15, 16, 1718, 19 and displayed good compatibility across patient orientations, treatment techniques, and systems 20, 21…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge‐based radiotherapy treatment planning is deemed to reduce the inter‐planner varieties of plan quality1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 and expedite the planning process 14, 15, 16, 1718, 19 and displayed good compatibility across patient orientations, treatment techniques, and systems 20, 21…”
Section: Introductionmentioning
confidence: 99%
“…Such differences may limit the desired organs‐at‐risk (OAR) sparing and the target coverage that can be achieved. Recent investigations have demonstrated that knowledge based planning (KBP), which utilizes a library of previously treated patient plans, has enormous potential for improving the quality and consistency of treatment plans …”
Section: Introductionmentioning
confidence: 99%
“…When comparing to previously published studies, for the tumour site of PSV a thorough summary has recently been presented by Heijmen et al [26]; with 12 studies identified as demonstrating small differences between automated and manual plans [2,10,18,[27][28][29][30][31][32][33][34][35], and only their more recent multi-centre study showing the overall dosimetric superiority of automation through reduced rectum doses [26]. For PPN, to the authors' knowledge two studies have been published.…”
Section: Discussionmentioning
confidence: 99%